1994
DOI: 10.1105/tpc.6.6.777
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Seed Transmission of a Plant Virus: Genetic and Structural Analyses of Pea Embryo Invasion by Pea Seed-Borne Mosaic Virus.

Abstract: Pea seed-borne mosaic virus (PSbMV), a seed-transmitted virus in pea and other legumes, invades pea embryos early in development. This process is controlled by maternal genes and, in a cultivar that shows no seed transmission, is prevented through the action of multiple host genes segregating as quantitative trait loci. These genes control the ability of PSbMV to spread into and/or multiply in the nonvascular testa tissues, thereby preventing the virus from crossing the boundary between the maternal and progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 21 publications
1
30
0
1
Order By: Relevance
“…The observation that seed transmission is affected by multiple determinants in the viral genome agrees well with the results of Wang & Maule (1994) who demonstrated that resistance to seed transmission in P. sativum involves several nuclear genes. This suggests that several virus-host factor interactions determine the spread and accumulation of PSbMV in the maternal testa tissue.…”
Section: Seed Transmission Of Vp-1114 Vp-1144 Vp-4144 and Vp-4111 Isupporting
confidence: 90%
See 2 more Smart Citations
“…The observation that seed transmission is affected by multiple determinants in the viral genome agrees well with the results of Wang & Maule (1994) who demonstrated that resistance to seed transmission in P. sativum involves several nuclear genes. This suggests that several virus-host factor interactions determine the spread and accumulation of PSbMV in the maternal testa tissue.…”
Section: Seed Transmission Of Vp-1114 Vp-1144 Vp-4144 and Vp-4111 Isupporting
confidence: 90%
“…The region of HCpro contained in HCpro N affects aphid transmission, replication (Atreya et al, 1992) and long-distance movement (Cronin et al, 1995). Wang & Maule (1994) demonstrated that the suspensor can act as a channel for transmission of PSbMV to the embryo proper. A prerequisite for embryo infection is, therefore, that virus reaches the micropylar region of the testa before disintegration of the suspensor.…”
Section: Seed Transmission Of Vp-1114 Vp-1144 Vp-4144 and Vp-4111 Imentioning
confidence: 99%
See 1 more Smart Citation
“…While differences in seed transmission of Pea seed borne mosaic virus (PSbMV) were associated with the inability of poorly seed-transmitted virus isolates to invade embryos (42), Bowers and Goodman (6) reported that cultivar-specific differences in seed transmission of a severe isolate of SMV were related to differences in the abilities of SMV strains to remain infectious within maturing embryos. Seed-transmissible strains of PSbMV were shown to enter developing embryos through a transient symplastic pathway that connects the base of the suspensor to the developing embryo (37).…”
mentioning
confidence: 99%
“…It should be noted that there are two distinct routes leading to seed transmissibility of a particular virus in a particular plant host; infected embryo from an infected mother plant or fertilization of an ovule of a virus free mother plant with infected pollen originating from another infected plant [15,16,26,33]. Regardless of the route, a virus must be capable of crossing the boundary between the non-productive and productive tissues in an infected plant in order for seed transmission to occur [26].…”
Section: Discussionmentioning
confidence: 99%